2020
DOI: 10.2807/1560-7917.es.2020.25.9.2000178
|View full text |Cite
|
Sign up to set email alerts
|

First cases of coronavirus disease 2019 (COVID-19) in the WHO European Region, 24 January to 21 February 2020

Abstract: In the WHO European Region, COVID-19 surveillance was implemented 27 January 2020. We detail the first European cases. As at 21 February, nine European countries reported 47 cases. Among 38 cases studied, 21 were linked to two clusters in Germany and France, 14 were infected in China. Median case age was 42 years; 25 were male. Late detection of the clusters’ index cases delayed isolation of further local cases. As at 5 March, there were 4,250 cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
292
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 484 publications
(330 citation statements)
references
References 5 publications
7
292
1
9
Order By: Relevance
“…15 In the first report of COVID-19 from the WHO European Region, a low frequency of gastrointestinal symptoms was also found. 14 In contrast, among 140 cases also from Wuhan, Zhang J-J et al, reported a higher frequency (39.6%) of gastrointestinal symptoms. In their series, nausea was the most common symptom while the frequency of diarrhea was very similar (12.9%).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…15 In the first report of COVID-19 from the WHO European Region, a low frequency of gastrointestinal symptoms was also found. 14 In contrast, among 140 cases also from Wuhan, Zhang J-J et al, reported a higher frequency (39.6%) of gastrointestinal symptoms. In their series, nausea was the most common symptom while the frequency of diarrhea was very similar (12.9%).…”
Section: Resultsmentioning
confidence: 94%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Thirteen papers were from China, 5-13, 15-17, 19 one from Singapore, 18 and one from the World Health Organization European Region. 14 (Table 1) These papers analyzed a total of 2800 patients. Of them 210 (7.5%) reported diarrhea, 125 (4.5%) nausea, 124 (4.4%) anorexia, 15 (0.5%) abdominal pain, 9 (0.3%) belching and reflux, and 7 (0.25%) patients from one study reported a combination of different symptoms (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Case fatality rates (CFR), not accounting for delays, were calculated by age and sex and smoothed with the locally weighted regression method. CFRs by age were also calculated by calendar period of diagnosis (i.e., before 4 th , [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. A multilevel (clustered by Region/AP) multivariable logistic model was applied to evaluate characteristics associated with death, including age group (i.e., ≤40, 40-49, 50-59, 60-69, 70-79, 80-89, 90+ years), sex, HCW status, and week of diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…With the aim to increase the understanding of the disease dynamics in Italy and support the planning of public health actions, a case-based surveillance system was established on the 27 th of February 2020, building on a previously existing surveillance system focused only on suspected and confirmed COVID-19 severe respiratory infections (12). The system contains data on all laboratory confirmed cases of COVID-19 as per the case definition published and regularly updated online by the European Centre for Disease Prevention and Control (ECDC) (13).…”
Section: The Italian Integrated Covid-19 Surveillance Systemmentioning
confidence: 99%
“…The analysis of the first 7,755 cases of COVID-19 in Korea showed a first increase of cases in specific geographic region comparable to the epidemiological situation in China and Italy (4,5). In Korea, despite a relevant number of cases per week in late February and early March, the peak seemed to have levelled off, yet the first wave did not go away.…”
Section: Discussionmentioning
confidence: 71%